Penanaman Nilai Pendidikan Multikultural di SDN 4 Kota Besi Hulu - Muhammad Zikri Hardana; Normuslim Normuslim; Rahmad Rahmad (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The researcher discovered an issue with students' intolerant behavior at school, specifically bullying their peers who held different ideas from them. This is another reason why it is necessary to promote multicultural education values. Based on the issues raised, the researcher was interested in the school and wanted to know: 1) whether and what multicultural education values were taught there; 2) how multicultural education values were taught there; and 3) what factors supported and hindered multicultural education values in the school. The teaching of multicultural education values at SDN 4 Kota Besi Hulu, Central Kalimantan Province, is the subject of this descriptive study utilizing a qualitative methodology. Techniques for gathering data include documentation, interviews, and observation. The principal, the vice principal of the curriculum department, the fifth grade teacher, and the fifth grade pupils at SDN 4 Kota Besi Hulu served as the study's data sources. The study's findings show that teachers at SDN 4 Kota Besi Hulu are instilling multicultural education values, including tolerance, moderation, and cultural friendliness. 1) Teachers instill the value of tolerance through classroom instruction, which is also incorporated into students' daily routines; 2) Teachers instill the value of moderation by implementing instruction and incorporating it into a learning process; and 3) Teachers instill culturally friendly values by making use of the significant days that each belief holds. These principles ensure that multicultural education values are instilled at SDN 4 Kota Besi Hulu